2019
DOI: 10.1103/physrevphyseducres.15.020108
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing use of regression models in physics education research: A review of hierarchical linear modeling

Abstract: This paper is part of the Focused Collection on Quantitative Methods in PER: A Critical Examination.] Physics education researchers (PER) often analyze student data with single-level regression models (e.g., linear and logistic regression). However, education datasets can have hierarchical structures, such as students nested within courses, that single-level models fail to account for. The improper use of single-level models to analyze hierarchical datasets can lead to biased findings. Hierarchical models (als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 112 publications
1
44
0
Order By: Relevance
“…Our models were all two‐level HLMs with student data in the first level and course data in the second level. Using HLMs allowed us to account for the nested nature of our dataset (Van Dusen & Nissen, in press). We explored whether including a third level for institution improved our models, but we found that it increased the total variance and did not substantively change the model coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…Our models were all two‐level HLMs with student data in the first level and course data in the second level. Using HLMs allowed us to account for the nested nature of our dataset (Van Dusen & Nissen, in press). We explored whether including a third level for institution improved our models, but we found that it increased the total variance and did not substantively change the model coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…AICc scores take into account the explanatory power of each variable without overly weighting model parsimony. While it is a common practices to use variance explained to select a final model (e.g., our own prior work [86,87]), using it to select models when investigating marginalized populations risks the models falling prey to a tyranny of the masses. Using predicted variance to select variables risks excluding marginalized students from groups with small representations in the data because the variance explained by a variable is proportional to its the sample size.…”
Section: B Data Analysismentioning
confidence: 99%
“…To examine whether the nested structure of our data necessitated the use of hierarchical models, we generated an unconditional model without predictor variables and calculated the intra-class correlation [88]. We found 8.6% of the variance at the course level; therefore, the best practice was to account for the hierarchical structure of the data in our model [87].…”
Section: B Data Analysismentioning
confidence: 99%
“…Our models were 2-level hierarchical linear models with student data in the first level and course data in the second level. Using hierarchical linear models allowed us to account for the nested nature of our dataset [32]. We developed the models and pooled the results for the imputed datasets using the mitml [33] and lme4 [34] packages in R. We developed the models through a step-wise addition of variables.…”
Section: Methodsmentioning
confidence: 99%